Assessment of Background Ionizing Radiation Levels at Selected Dumpsites in Obio/Akpor Local Government Area, Rivers State, Nigeria - Nwii, Abayiga Abel; Gbarato, Oliver; Biibaloo, Livinus Legborsi (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
The assessment of background ionizing radiation level of dumpsite along international Airport road of Obio/akpor has been conducted using a well calibrated radiation metre (Radalert 200). Twenty (20) selected sampling points was considered within the dumpsite for the measurement of the radiation exposure. The background ionizing radiation (BIR) of the Dump site variation is within 0.010 to 0.017 mR/hr and mean of 0.014±0.002 (mR/hr), The absorbed dose varies from 87.0 to147.9 nGy/hr with mean of 121.8 nGy/hr, with a mean of 0.21 mSv/yr, the Annual Effective Dose Equivalent (AEDE) is lower than the UNSCEAR (2000). It ranges from 0.14 to 0.27 mSv/yr. The testes have the largest organ dosage, according to the computed doses of the other bodily organs. of 0.162mSy-1 with eighteen percentages (18%) and ovary have the lowest of 0.115mSy-1 with thirteen percentages (13%) as shown in figure 5, the organ dose value were below the recommended safe limit. The excess lifelong risk of cancer (ELCR) varies from 0.49 to 0.91x10-3 with mean of 0.74x10-3 which is greater than stipulated standard. Conclusively the high value of the associated radiological parameters and radiation exposure value within the dumpsite may be dangerous to residents and workers within the dumpsite. Therefore, the dumpsites should be properly monitor by the regulatory authorities in order to alleviate the health effects on the workers.